Establishment of a mandible defect model in rabbits infected with multiple bacteria and bioinformatics analysis - Zhao, Yuan; Su, Jun; Xu, Chong-yan; Li, Yan-bo; Hu, Tong; Li, Yi; Yang, Li; Zhao, Qiang; Zhang, Wen-yun (Frontiers in Bioengineering and Biotechnology, 2024)
Objective: A model of chronic infectious mandibular defect (IMD) caused by mixed infection with Staphylococcus aureus and Pseudomonas aeruginosa was established to explore the occurrence and development of IMD and identify key genes by transcriptome sequencing and bioinformatics analysis. Methods: S. aureus and P. aeruginosa were diluted to 3×108 CFU/ml, and 6×3×3 mm defects lateral to the Mandibular Symphysis were induced in 28 New Zealand rabbits. Sodium Morrhuate (0.5%) and 50 μL bacterial solution were injected in turn. The modeling was completed after the bone wax closed; the effects were evaluated through postoperative observations, imaging and histological analyses. Gene Ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway, and protein‒protein interaction (PPI) network analyses were performed to investigate the function of the differentially expressed genes (DEGs). Results: All rabbits showed characteristics of infection. The bacterial cultures were positive, and polymerase chain reaction (PCR) was used to identify S. aureus and P. aeruginosa. Cone beam CT and histological analyses showed inflammatory cell infiltration, pus formation in the medullary cavity, increased osteoclast activity in the defect area, and blurring at the edge of the bone defect. Bioinformatics analysis showed 1,804 DEGs, 743 were upregulated and 1,061 were downregulated. GO and KEGG analyses showed that the DEGs were enriched in immunity and osteogenesis inhibition, and the core genes identified by the PPI network were enriched in the Hedgehog pathway, which plays a role in inflammation and tissue repair; the MEF2 transcription factor family was predicted by IRegulon. Conclusion: By direct injection of bacterial solution into the rabbit mandible defect area, the rabbit chronic IMD model was successfully established. Based on the bioinformatics analysis, we speculate that the Hedgehog pathway and the MEF2 transcription factor family may be potential intervention targets for repairing IMD.